2017
DOI: 10.1016/j.canlet.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells in osteosarcoma

Abstract: Abstract:Osteosarcoma is the most common primary bone tumour in children and adolescents and advanced osteosarcoma patients with evidence of metastasis share a poor prognosis.Osteosarcoma frequently gains resistance to standard therapies highlighting the need for improved treatment regimens and identification of novel therapeutic targets. Cancer stem cells (CSC) represent a sub-type of tumour cells attributed to critical steps in cancer including tumour propagation, therapy resistance, recurrence and in some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
187
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(201 citation statements)
references
References 44 publications
1
187
0
Order By: Relevance
“…Whatever, several groups have demonstrated that extracellular vesicles represent an important way of communication between mesenchymal stem cells and osteosarcoma cells [51,52]. Under stress environment such as local acidosis associated to tumor growth and peritumoral osteolysis, mesenchymal stem cells could secrete extracellular vesicles carrying proteins, mRNA and microRNA modulating osteosarcoma cell proliferation and stemness [14,51,52]. Acquired stemness properties (e.g.…”
Section: Mesenchymal Stem Cells Control Osteosarcoma Development: Potmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever, several groups have demonstrated that extracellular vesicles represent an important way of communication between mesenchymal stem cells and osteosarcoma cells [51,52]. Under stress environment such as local acidosis associated to tumor growth and peritumoral osteolysis, mesenchymal stem cells could secrete extracellular vesicles carrying proteins, mRNA and microRNA modulating osteosarcoma cell proliferation and stemness [14,51,52]. Acquired stemness properties (e.g.…”
Section: Mesenchymal Stem Cells Control Osteosarcoma Development: Potmentioning
confidence: 99%
“…Indeed, based on the "seed and soil' theory of Paget, it is now well recognized that osteosarcoma, like other cancers, requires an adequate local microenvironment for its development [11,12]. This microenvironment can provide all metabolites and factors for the control of proliferation, drug resistance, dissemination or/and dormancy of osteosarcoma cells [5,[13][14][15]. Then, the pressure exerted by microenvironment may be responsible for a specific selection of osteosarcoma cells with predominant specificities such as a high quiescent or a proliferative profile.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of multipotency with LDA for the identification of CSCs is the best method of evaluation (Hill & Perris, ). Choosing each method to separate CSC from different cell classes shows us that each CSC has a different property and show a unique and specific feature (H. K. Brown, Tellez‐Gabriel, & Heymann, ).…”
Section: Multipotencymentioning
confidence: 99%
“…CSCs are characterized by self-renewal and differentiation potential, which endow the potential of drug resistance, relapse and metastasis for cancer cells [5]. Increasing evidence have illustrated the critical role of CSCs in the osteosarcoma tumorigenesis, involved in differentiation, invasion and metastasis [6,7].…”
Section: Introductionmentioning
confidence: 99%